Flint Hills Land, Sky, and People - Cathy Hoy; Jim Hoy; Marty White (Symphony in the Flint Hills, 2014)
If you have spent time in the Flint Hills of Kansas, you will understand the restorative emotions that inspire the theme chosen for the 2014 Symphony in the Flint Hills Field Journal—Flint Hills Land, Sky, and People. This is the introduction for the content of the Field Journal.
Keywords: Flint Hills; Land; sky; people; introduction; geological; spiritual